A Multiserver User-space Unikernel for a Distributed Virtualization System - Pessolani, Pablo (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2019)
Nowadays, most Cloud applications are developed using Service Oriented Architecture (SOA) or MicroService Architecture (MSA). The scalability and performance of them is achieved by executing multiple instances of its components in different nodes of a virtualization cluster. Initially, they were deployed in Virtual Machines (VMs) but, they required enough computational, memory, network and storage resources to hold an Operating System (OS), a set of utilities, libraries, and the application component. By deploying hundreds of these application components, the resource requirements increase a lot. To minimize them, usually small footprint OS are used. Later, as management tools were improved, the application components began to be deployed in Containers which require even less resources than VMs. Another way to reduce the resource requirements is integrating the application components in a Unikernel. This article proposes a Unikernel called MUK, based on a multiserver OS, to be used as a tool to integrate Cloud application components. MUK was built to run in user-space inside a Container of a Distributed Virtualization System. Both technologies facilitate the scattering of application components in a virtualization cluster keeping the isolation properties and minimal attack surface of a Unikernel.